Grundtvig og de latinske salmer - Elbek, Jørgen (Grundtvig-Studier, 1959)
Grundtvig and the Latin Hymns. By Jørgen Elbek. 1. Purpose and Problems of the New Versions. Translations into Danish from Latin play no important part in Danish hymnody until Grundtvig’s about thirty reproductions in his Sang-Værk til den danske Kirke 1836-37 (Collection of Hymns for the Danish Church - SV). The background of this untraditional element will appear from an analysis of Grundtvig’s opinions on hymn writing as expressed in letters and in a review: First the SV must be regarded as a collection of material for a new hymnbook to be edited, and Grundtvig has consequently tried “to collect into it all Christian tones to enable everybody to find his own”. The Latin hymns contribute to this multiplicity. Secondly the SV is an expression of Grundtvig’s conception of the history of the Church which emanate from his allegorical interpretation of the letters to the churches in the Revelation of St. John: the Church consists of 7 national Churches (Folke-Menigheder) of which the Latin is the third. All this Churches are represented in the SV - the Latin by these Latin hymns. Thirdly the SV is intended as a harbinger to announce the approach of the universal hymn of thanksgiving to appear as the unalloyed Christian extract of the nationally coloured hymns in existence. For which reason the Latin hymns are indispensable. These three views may very well be considered one, but a contrary view is also voiced: Every hymn writer is tied to his own individuality and background; and his Christianity can therefore only be conveyed pari passu with an expression of his individual characteristic which will cut him off from the universal Christian community. Pursueing this line of thought we arrive at a conception of Grundtvig’s reproductions not as hymns belonging to the universal Church, but to a more narrow community, Danish-Latin, or merely Danish. This tension between common and individual Christianity is the condition under which the new versions were created. 2 . Sources. In the foot-notes of his reproductions Grundtvig has given their originals, but the fact that these exist in several versions will render it necessary to demonstrate which editions have been used. The inventories of Grundtvig’s library and the ledger of the Royal Library show that Grundtvig has had direct access to fourteen editions of hymns. By means of the reproductions the originals of which are found in one of the editions only can be seen which editions are safe sources. That these editions are also the source of the remaining translations is rendered probable when the variant readings of the originals are compared with the text of the reproduction, which method is also applied when the original is found in more than one of the editions which are considered safe sources. The result is that by far the most of the reproductions in the SV can be traced back to I. Clichtoveus’ “Elucidatorium ecclestiasticum”, Basel 15 17, an bundant and well annotated edition, but some to A. J. RambacWs “Anthologie christlicher Gesänge I ”, Altona 1817, with abbreviated texts and incongenial commentary. The few translations dating from the years before and after the SV build upon poor second-rate sources. 3 . Grundtvig as a Translator. The style of the Latin hymns differs greatly from both antique and modem poetry. The beauty they seek to reflect is not accessible to senses but only to intellect, to contemplation. In its most pronounced form the style has the appearance of a system in which the elements are few, but the relations numerous - symbol of the immaterial beauty of Divinity. The composition is made not by the elaboration of a motif organically coherent but by the filling in of a framework. The metaphors, of which the greater number is biblical, have no illustrative value but serve as objective documentations from the Holy Writ. Of other important stylistic figures can be mentioned the antithesis, representing the contrasts within the Christian picture of the world, and the annominatio expressing the similarities contained within these contrasts. The stylistic figures are also sonorous figures; correspondence in the meaning of the words being underlined by correspondence in sound. In prosody the development of hymnography is most clearly seen. Grundtvig’s versions are filled with all the features which the hymnographers attempted to avoid. Their style is alien to thought and contemplation, but appeals to spontaneous feeling and imagination. The composition is changed in an effort to make the theme one coherent and tangible whole. The metaphors have illustrative and suggestive functions. The antithesis is provided with additional atmosphere by which the mere contrast is blurred. For linguistic reasons annominatio cannot well be transferred, Danish being without declension. Thus the intelligible side of the style of the hymns is lost, whereas regarding metre and rhythm some influence is exercised. The transplanting from one language to another has resulted in a work of a much more concrete character. Among the most successful may be pointed out the versions of the anonymous Urbs beata Hierusalem and Veni sancte spiritus (“The Golden Sequence”). 4. The Christianity of the Hymns. By their religious subjectmatter the reproductions are divided into two groups: In the hymns of the first group Christ is conceived as the hero of irresistible power and the Christians are his warriors armed to fight sin and death, confident of their reward. The links to the originals are very few indeed. Whereas these hymns are characterized by an uncomplicated self-realization, the problems of the ego appear in the reproduction of Salve mundi salutare by Arnoulf of Louvain: in the presence of the suffering Saviour the poet perceives “the hardness of the heart, the cold of the heart” and he prays to be allowed to join a Christian community where the barriers of self are demolished. The universal harmony which he has in view here is elucidated in the second group: truth and love is one thing, nature and history bear witness of the Divine. These ideas point toward Grundtvig’s versions of Adam of St. Victor’s Whitsuntide hymns. In these the singing congregation pray to become mature and merge into one spiritual community; its nature cannot be exhausted by abstract terms, only by an image. The connection with the originals Is intimate; even when the poet goes his own way, he is still in conformity with the original poets. The historical significance of the versions is obvious: they did not supply Danish hymn writing with a new style but they did add a number of new themes and thus extended the sphere of the genre. (The summary translated by Kurt Hansen, København).